Recent Developments in Sweat Analysis and Its Applications - Saima Jadoon; Sabiha Karim; Muhammad Rouf Akram; Abida Kalsoom Khan; Muhammad Abid Zia; Abdul Rauf Siddiqi; Ghulam Murtaza (International Journal of Analytical Chemistry)
Currently, the clinical use of sweat as biofluid is limited. The collection of sweat and its analysis for determining ethanol, drugs, ions, and metals have been encompassed in this review article to assess the merits of sweat compared to other biofluids, for example, blood or urine. Moreover, sweat comprises various biomarkers of different diseases including cystic fibrosis and diabetes. Additionally, the normalization of sampled volume of sweat is also necessary for getting efficient and useful results.